The multifaceted roles of matrix metalloproteinases in lung cancer - Wei, Cui (Frontiers in Oncology, 2023)
Background Though the matrix metalloproteinases (MMPs) are widely investigated in lung cancer (LC), however, almost no review systematically clarify their multi-faced roles in LC. Methods We investigated the expression of MMPs and their effects on survival of patients with LC, the resistance mechanisms of MMPs in anti-tumor therapy, the regulatory networks of MMPs involved, the function of MMPs inducing CSCLs, MMPs-related tumor immunity, and effects of MMP polymorphisms on risk of LC. Results High expression of MMPs was mainly related to poor survival, high clinical stages and cancer metastasis. Role of MMPs in LC are multi-faced. MMPs are involved in drug resistance, induced CSCLs, participated in tumor immunity. Besides, MMPs polymorphisms may increase risk of LC. Conclusions MMPs might be promising targets to restore the anti-tumor immune response and enhance the killing function of nature immune cells in LC.